If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(c + -8) + -3(2c + n) = -84 Reorder the terms: 5(-8 + c) + -3(2c + n) = -84 (-8 * 5 + c * 5) + -3(2c + n) = -84 (-40 + 5c) + -3(2c + n) = -84 -40 + 5c + (2c * -3 + n * -3) = -84 -40 + 5c + (-6c + -3n) = -84 Combine like terms: 5c + -6c = -1c -40 + -1c + -3n = -84 Solving -40 + -1c + -3n = -84 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '40' to each side of the equation. -40 + -1c + 40 + -3n = -84 + 40 Reorder the terms: -40 + 40 + -1c + -3n = -84 + 40 Combine like terms: -40 + 40 = 0 0 + -1c + -3n = -84 + 40 -1c + -3n = -84 + 40 Combine like terms: -84 + 40 = -44 -1c + -3n = -44 Add '3n' to each side of the equation. -1c + -3n + 3n = -44 + 3n Combine like terms: -3n + 3n = 0 -1c + 0 = -44 + 3n -1c = -44 + 3n Divide each side by '-1'. c = 44 + -3n Simplifying c = 44 + -3n
| -20+8n=-4(5-2n) | | 2g-13=4 | | 7x-5=5x-29 | | log(x)+log(x+1)=-1 | | 3n-5=2m+6 | | -9n-9=-23+5n | | 9x=0.012 | | 6x+5=-8+4x+19 | | 2/15=h/55 | | 21+(3-f)7=11 | | 2(s+3)-5s=30 | | y^-3•x^3y^-4/(y^3)^-2 | | 4f=.20*4 | | x-21=5x-9 | | -11n+8=-11n+11 | | 5r+5+2r+16=10 | | 20-x=10x | | 6(3f-9)=16c-60 | | 5w(4w-3)+21=2w(10w+1)-13 | | 8/3=8 | | 10x=-34+84 | | 35-10r+5r-5=65 | | 5z^1/4(3z^3/4-4z8) | | x^2-11x+56=0 | | 2(-5n-3)+6(n-8)=-7+n+8 | | (X^2+2x)= | | v-9a=4 | | -4(4x+9)=-36 | | 2y+5=-0 | | 4m-2=4m-2 | | 6,600/-44 | | 3=-1h |